(untitled) (Revista de Letras Norte@mentos, 2017)
This article discusses the collaborative process established by an in-service and a pre-service teacher within a continuing education program developed at a public school in the city of Santa Maria, RS. The results show that the teachers engaged themselves in the collaborative teaching practice and successfully oriented the students in the development of the proposed activities. In this sense, the teaching of English based on critical approaches can broaden the students’ engagement into social practices, contributing to their development as citizens (SCHLATTER, 2009).